Internal radiation dose assessment of radiopharmaceuticals prepared with cyclotron‐produced 99mTc. Issue 3 (8th February 2019) - Meléndez‐Alafort, Laura; Ferro‐Flores, Guillermina; De Nardo, Laura; Bello, Michele; Paiusco, Marta; Negri, Anna; Zorz, Alessandra; Uzunov, Nikolay; Esposito, Juan; Rosato, Antonio
Abstract : Purpose: Technetium‐99m ( 99m Tc) is the radioisotope most widely used in diagnostic nuclear medicine. It is readily available from 99 Mo/ 99m Tc generators as the β − decay product of the 99 Mo (T½  = 66 h) parent nuclide. This latter is obtained as a fission product in nuclear reactors by neutron‐induced reactions on highly enriched uranium. Alternative production routes, such as direct reactions using proton beams on specific target materials [ 100 Mo(p, 2n) 99m Tc], have the potential to be both reliable and relatively cost‐effective. However, results showed that the 99m Tc extracted from proton‐bombarded 100 Mo‐enriched targets contains small quantities of several Tc radioisotopes ( 93m Tc, 93 Tc, 94 Tc, 94m Tc, 95 Tc, 95m Tc, 96 Tc, and 97m Tc). The aim of this work was to estimate the dose increase (DI) due to the contribution of Tc radioisotopes generated as impurities, after the intravenous injection of four radiopharmaceuticals prepared with cyclotron‐produced 99m Tc (CP‐ 99m Tc) using 99.05% 100 Mo‐enriched metallic targets. Methods: Four 99m Tc radiopharmaceuticals (pertechnetate, sestamibi (MIBI), hexamethylpropylene‐amine oxime (HMPAO) and disodium etidronate (HEDP)) were considered in this study. The biokinetic models reported by the International Commission on Radiological Protection (ICRP) for each radiopharmaceutical were used to define the main source organs and to calculate the number of disintegrations per MBq that occurred in each source organ ( N source ) for each Tc radioisotope present in the CP‐ 99m Tc solution. Then, target organ equivalent doses and effective dose were calculated for each Tc radioisotope with the OLINDA/EXM software versions 1.1 and 2.0, using the calculated N source values and the adult male phantom as program inputs. Total effective dose produced by all Tc isotopes impurities present in the CP‐ 99m Tc solution was calculated using the fraction of total activity corresponding to each radioisotope and compared with the effective dose delivered by the generator‐produced 99m Tc. Results: In all cases, the total effective DI of CP‐ 99m Tc radiopharmaceuticals calculated with either versions of the OLINDA software was less than 10% from 6 up to 12 h after EOB. 94m Tc and 93m Tc are the Tc radioisotopes with the highest concentration in the CP‐ 99m Tc solution at EOB. However, their contribution to DI 6 h after EOB is minimal, due to their short half‐lives. The radioisotopes with the largest contribution to the effective DI are 96 Tc, followed by 95 Tc and 94 Tc. This is due to the types of their emissions and relatively long half‐lives, although their concentration in the CP‐ 99m Tc solution is five times lower than that of 94m Tc and 93m Tc at the EOB. Conclusions: The increase in the radiation dose caused by other Tc radioisotopes contained in CP‐ 99m Tc produced as described here is quite low. Even though the concentrations of the 94 Tc and 95 Tc radioisotopes in the CP‐ 99m Tc solution exceed the limits established by the European Pharmacopoeia, CP‐ 99m Tc radiopharmaceuticals could be used in routine nuclear medicine diagnostic studies if administered from 6 to 12 h after the EOB, thus maintaining the effective DI within the 10% limit.